The Goldberg–Huxley model of the pathway to psychiatric care: 21st-century systematic review - Peter Huxley; Anne Krayer; Rob Poole; Alicja Gromadzka; Daniel Lai Jie; Sadia Nafees (BJPsych Open, 2023)
Background The classification of mental disorders used to be based only on people seen by hospital psychiatrists. In fact, most people with a mental disorder were, and are, not seen by psychiatrists because of decisions made prior to psychiatric consultation. The first description of this ‘pathway’ to care and its levels and filters was published by Goldberg and Huxley in 1980.